2013
DOI: 10.1080/00140139.2013.765602
|View full text |Cite
|
Sign up to set email alerts
|

The natural angle between the hand and handle and the effect of handle orientation on wrist radial/ulnar deviation during maximal push exertions

Abstract: Manual materials handling (MMH) tasks involving pushing have been related to increased risk of musculoskeletal injury. This study shows that handle orientation influences hand and wrist posture during pushing, and suggests that the design of push handles on carts and other MMH aids can be improved by adjusting their orientation to fit the natural interface between the hand and handle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Following a more detailed assessment one study [17] was excluded due to similar content to a second study by the same author [2] and another one because it primarily focused on sex differences [18]. There were studies excluded for not meeting the inclusion criteria (Table 5) [5], [17], [18], [19], [20], [21], [22], [23], [24], [25]. Thirteen studies were retained after reading the whole paper and submitted to assessment of their methodological quality (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Following a more detailed assessment one study [17] was excluded due to similar content to a second study by the same author [2] and another one because it primarily focused on sex differences [18]. There were studies excluded for not meeting the inclusion criteria (Table 5) [5], [17], [18], [19], [20], [21], [22], [23], [24], [25]. Thirteen studies were retained after reading the whole paper and submitted to assessment of their methodological quality (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…EMGs of the upper and lower limbs were recorded during the STS movement. Several studies have investigated the effects of handle orientation on the pull and push forces (Young, et al, 2009;Seo, et al, 2010;Lin, et al, 2012;Ehrlich, et al, 2013;Young, et al, 2013). They suggested that the maximum pull and push forces occur when the forearm is in line with the forces and the wrist is in the neutral posture.…”
Section: Introductionmentioning
confidence: 99%